2011
DOI: 10.1002/mame.201100203
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Blends From Plasticized Soy Meal, Polycaprolactone, and Poly(butylene succinate)

Abstract: A synergistic effect of simultaneous plasticization and destructurization of soy protein in melt extrusion is studied using soy meal, glycerol, and urea. The combined effect of plasticization and destructurization yields thermoplastic soy meal (TSM) that is capable of chemical interactions with biodegradable polyesters. Melt‐compounded blends of TSM with biodegradable polyesters give new ductile bioplastics. The observed improvement in the properties of these blends might be due to two reason; the high elastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 39 publications
(42 reference statements)
0
33
0
Order By: Relevance
“…The morphology of the polymer blend plays a critical role in understanding the structure-property relationships between the blend components, and hence there has been much research on structure development in such blends. Several studies were conducted on evaluating the morphology of PCL/PBS blends by employing scanning electron microscopy (SEM) and polarized light optical microscopy (PLOM) [16,17,[19][20][21]27]. These blends were mostly prepared through melt blending and solution mixing methods.…”
Section: Pcl/pbs Blends 21 Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…The morphology of the polymer blend plays a critical role in understanding the structure-property relationships between the blend components, and hence there has been much research on structure development in such blends. Several studies were conducted on evaluating the morphology of PCL/PBS blends by employing scanning electron microscopy (SEM) and polarized light optical microscopy (PLOM) [16,17,[19][20][21]27]. These blends were mostly prepared through melt blending and solution mixing methods.…”
Section: Pcl/pbs Blends 21 Morphologymentioning
confidence: 99%
“…Although blending is a good method for improving the properties of the individual polymers, the PCL/PBS blends are immiscible as evidenced by composition independent T g s and a bi phasic melt, which leads to poor interfacial adhesion and macrophase separation. Several methods, such as the addition of the copolymers (poly (ethylene oxide)-block-poly(propylene oxide)-blockpoly(ethylene oxide) (PEO-PPO-PEO) and poly(butylene succinate-co-ɛ-caprolactone) (P(BS-co-CL)) and thermoplastic soy meal (TSM), have been applied to improve miscibility, interfacial adhesion and the resultant mechanical properties of PCL/PBS blends [16,20,21]. Recent reports [37][38][39] revealed that adding conductive carbon-based nano-fillers such as carbon nanotubes (CNTs) into PCL and PBS matrices can enhance some of the matrix properties to better levels than those of the copolymers or polymers filled with metal powders, as well as produce electrically conductive materials with better mechanical properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many efforts have been made to discover, develop and modify biodegradable polymers derived from renewable resources [3].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, many efforts have been made by materials scientists and engineers to discover, develop and modify of biodegradable polymers derived from renewable resources [3]. Polybutylene succinate (PBS) is one of the biodegradable thermoplastic polyesters which can prepared from butanediol and succinic acid produced by fermentation process [4,5].…”
Section: Introductionmentioning
confidence: 99%